Physician's Legal Responsibilities in Providing Medicines Outside the National Formulary to National Health Insurance Participants - Vinandita Nabila Karina; Mokhamad Khoirul Huda; Mohammad Zamroni (SOEPRA, 2022)
Abstract: Doctors who give drugs outside the national formulary to National Health Insurance (JKN) participants have caused several polemics. Due to complaints from JKN participants, the government issued regulations regarding the preparation of the implementation of the National Formulary in administering the health insurance program. This hierarchy caused the Minister of Health to issue Regulation of the Minister of Health of the Republic of Indonesia Number 54 of 2018 Concerning the Preparation of the Implementation of the National Formulary. The purpose of this study was to analyze the legal ratio of the drug formulary in the National Health Insurance System and to analyze the liability of doctors who provide drugs outside the national formulary to National Health Insurance participants. This type of research uses a statute approach, a conceptual approach and a case approach. The statutory approach (statute approach) and the concept approach (conceptual approach). The legal material analysis method is deductive. The findings show that the legal ratio of drug formularies in the National Health Insurance System is caused by the existence of legal regulations regarding FORNAS due to problems that occur, including incompatibility with FORNAS and the e-catalogue, the FORNAS amendment rules apply retroactively violating the principle of legal certainty, there are no minimum rules of conformity. FORNAS in the Hospital/Region Formulary so that the Ministry of Health issues regulations regarding the preparation of drug lists with the issuance of regulations regarding FORNAS.; 2) The legal responsibility of doctors who give medicines outside the national formulary to National Health Insurance (JKN) participants includes the prescribing error stage regarding all requests for prescriptions based on the responsibility of doctors' ethical norms as well as legal responsibility based on civil, criminal and legal provisions. administration.Keywords: doctor, law, responsibility and JKN Abstrak: Dokter yang memberikan obat di luar formularium nasional pada peserta Jaminan Kesehatan Nasional (JKN) menimbulkan beberapa polemik. Adanya keluhan peserta JKN tersebut maka pemerintah menerbitkan aturan tentang penyusunan penerapan Formularium Nasional dalam penyelenggaraan program jaminan kesehatan. Hirarki tersebut menyebabkan Menteri Kesehatan telah mengeluarkan Peraturan Menteri Kesehatan Republik Indonesia Nomor 54 Tahun 2018 Tentang Penyusunanan Penerapan Formularium Nasional. Tujuan penelitian ini adalah untuk menganalisis rasio legis formularium obat dalam Sistem jaminan Kesehatan Nasional dan untuk menganalisis pertanggungjawaban dokter yang memberikan obat di luar formularium nasional pada peserta Jaminan Kesehatan Nasional. Tipe penelitian ini menggunakan pendekatan perundang-undangan (statute approach), pendekatan konsep (conceptual approach) dan pendekatan kasus (case approach). Pendekatan perundang-undangan (statute approch) dan pendekatan konsep (conceptual approach). Metode analisis bahan hukum adalah metode deduktif. Hasil temuan menunjukkan rasio legis formularium obat dalam Sistem Jaminan Kesehatan Nasional disebabkan dari adanya regulasi hukum tentang fornas disebabkan adanya permasalahan-permasalahan yang terjadi antara lain ketidaksesuaian FORNAS dan e-catalogue, aturan perubahan FORNAS berlaku surut melanggar asas kepastian hukum, belum ada aturan minimal kesesuaian FORNAS pada Formularium RS/Daerah sehingga Kementrian Kesehatan menerbitkan peraturan tentang penyusunan daftar obat dengan dikeluarkannya peraturan tentang FORNAS.; 2) Tanggung jawab hukum dokter yang memberikan obat di luar formularium nasional pada peserta Jaminan Kesehatan Nasional (JKN) meliputi tahap Prescribing error menyangkut segala permintaan dalam resep didasarkan tanggung jawab norma etik dokter serta tanggung jawab hukum yang didasarkan pada ketentuan hukum perdata, pidana, dan administrasi. Kata kunci: dokter, hukum, tanggung jawab dan JKN